Phenomenological Study: The Impact of Islamic Education on Indigenous Communities Wetu Telu Bayan - Sumiadi, Raden (JUPE : Jurnal Pendidikan Mandala, 2024)
The Wetu Telu Bayan indigenous people are a community group that still maintains local traditional values in the midst of the progress of the times. They received Islamic teachings in the early phase, therefore the traces of the implementation of Islamic education still exist today. This research is designed with a phenomenological approach. Data was obtained through interviews, observations and FGD activities involving informants from traditional leaders, indigenous peoples, school principals, and teachers. The data obtained were then analyzed using the Miles and Huberman model. The validity of the data was confirmed through the extension of the observation period and triangulation. The results of the study show that since the occurrence of Islamic educational accommodation in the Wetu Telu Bayan indigenous people, several impacts have occurred, such as changes in knowledge of Islamic practices and their customs. Some of the indigenous people practice perfect Islamic practices such as prayer, zakat, fasting and hajj. In addition, some parents from indigenous peoples also send their children to Islamic boarding schools or other religious schools, such a condition that gives birth to the Wetu Telu Inclusive type indigenous people.